Community Legal Awareness in Waste Management in Cirebon City - Achmad Tristianoka; Muhamad Ikbal; Yuda Rizki Mahesa; Dudung Hidayat; Diky Dikrurahman (Publikasi Indonesia, 2024)
Waste management is still an important challenge in urban areas, including Cirebon City, Indonesia, because of its significant environmental and social impacts. This study explores community legal awareness regarding waste management practices in Cirebon, emphasizing the importance of a comprehensive approach and community participation. Through qualitative research involving interviews and participant observation with 50 stakeholders, including community leaders, environmental NGOs, sanitation workers, and residents, this research identifies the main factors influencing legal awareness and proposes strategies to increase community involvement. Findings show a gap between knowledge and action, highlighting infrastructure deficiencies and low community participation. These recommendations emphasize the need for improved policy frameworks, improved infrastructure, targeted education, and collaborative governance to encourage sustainable waste management and environmental health in Cirebon.